Impact of using the international association of diabetes and pregnancy study groups criteria in South Auckland: prevalence, interventions and outcomes. (11th October 2014) - Ekeroma, Alec J.; Chandran, Gokilavani S.; McCowan, Lesley; Ansell, David; Eagleton, Carl; Kenealy, Tim
<x xml:space="preserve">Abstract</x> Introduction Adopting the modified International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria for diagnosing gestational diabetes mellitus (GDM) will increase the prevalence of GDM resulting in increased resource utilisation and an unknown effect on clinical outcomes. Aims To determine the prevalence of GDM by the modified IADPSG criteria and compare characteristics and pregnancy outcomes between women with GDM by IADPSG‐additional, those with GDM by the New Zealand Society for the Study of Diabetes (NZSSD) criteria and those with a normal oral glucose tolerance test (OGTT). Methods All women who delivered at Counties Manukau District Health Board (CMDHB) for a 12‐month period from July 2012 to June 2013 had demographic, pregnancy and laboratory data obtained from hospital databases and clinical records. Results Of the 6376 (85%) of eligible women screened for GDM, 381 (6%) had GDM by NZSSD criteria and an additional 238 (4%) by the modified IADPSG‐additional criteria, a relative increase of 62%. Women with GDM by NZSSD criteria had similar characteristics compared to women with GDM by IADPSG‐additional. The outcomes between the two groups were also similar with the exception of a higher induction of labour (IOL) rate in women with GDM by NZSSD and a higher mean birthweight in the GDM by IADPSG‐additional. Conclusion Adopting the modified IADPSG criteria will result in a 62% increase in the number of GDM cases with a significant impact on workload and resources. Currently, there is insufficient evidence to support the introduction of the IADPSG criteria for our service.